FORENSIC MEDICINE FACE TO FACE WITH MEDICAL NEGLIGENCE (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
While conducting autopsies, a doctor often comes across a case, which shows a chance evidence of obvious gross medical negligence. But due to systemic restrictions, he cannot take an initiative to report such cases in a manner where in the affected families can get due compensations. His dilemma is further enhanced by the fact that the lay people and the law enforcement agencies are not in a position to take cognizance in such cases. While highlighting three such case reports, the paper has made an attempt to discuss such problems. The obvious remedies involve a positive role to be played by the subject of Forensic Medicine, which will also help to enhance the standards of patient care and reducing the incidents of medical negligence.
Keywords: dilemma; autopsies,